Gate-Recessed Normally-OFF GaN MOSHEMT With Improved Channel Mobility and Dynamic Performance Using AlN/Si3N4 as Passivation and Post Gate-Recess Channel Protection Layers - Liu, Shaofei; Wang, Maojun; Ming Tao; Yin, Ruiyuan; Gao, Jingnan; Sun, Haozhe; Wei Lin; Wen, Cheng P.; Wang, Jinyan; Wu, Wengang; Hao, Yilong; Zhang, Zhaofu; et al. (IEEE ELECTRON DEVICE LETTERS, 2017)
In this letter, a gate recessed normally-off GaN metal-oxide-semiconductor high-electron-mobility transistor on silicon substrate is fabricated using AlN/Si3N4 as the passivation layer. The thin AlN layer serves the dual role of protecting the gate channel region from direct plasma bombardment during the RIE Si3N4 removal and passivating the surface states in the access region. As a result, the effective carrier mobility in the normally-off channel is found to improve from the 568 cm(2)/V . s in conventional Si3N4 passivation process to a high value of 1154 cm(2)/V . s. A saturated output current density of 603 mA/mm and an ON-resistance of 5.3 Omega . mm was obtained for devices with L-G/L-GS/L-GD/W-G = 1.5/1.5/3/20 mu m. Meanwhile, the degradation of dynamic ON-resistance is significantly suppressed due to the effective passivation of surface states by the AlN layer grown by plasma-enhanced atomic layer deposition.